Evaluation of Genetic Polymorphisms for Determining Steroid Response in Nephrotic Children - Kara, Aslihan; Gurgoze, Metin Kaya; Kara, Murat; Aydin, Mustafa (Assoc Clinical Scientists, 2018)
Goals. Although all children with nephrotic syndrome (NS) have similar biochemical abnormalities and clinical manifestations, they seem to have variable grades of steroid responsiveness and patterns of disease relapse. Therefore, this study aimed to examine whether steroid metabolism-related genetic polymorphisms, which are responsible for drug elimination, play a role for steroid response in children with NS. Methods. The study population consisted of 53 children with idiopathic NS [45 steroid sensitive (SS) and 8 steroid resistant (SR) nephrotic patients] and 22 healthy children as the control group. The genetic polymorphisms of the multi-drug resistance-1 (MDR-1) and human cytochrome P450 3A (CYP3A4 and CYP3A5) genes were analyzed and compared between SS, SR and control groups. In addition, mutations in the podocin and nephrin genes were also investigated. Results.There was no statistically significant difference between NS and control groups in terms of age and gender (P>0.05). Although the NS was more prevalent in boys (39/53, 73.6%), females were more dominant in the SR group (5/8, 62.5%). Serum urea and creatinine values were significantly higher in the SR group than in the SS group. Mutations in the podocin and nephrin genes were not different between the groups (P>0.05). In addition, no difference was found between the groups in regard to the polymorphisms of the MDR-1, CYP3A4 and CYP3A5 genes (P>0.05). Conclusion. These results showed that the polymorphisms of the MDR-1, CYP3A4 and CYP3A5 genes were not associated with steroid response.
Keywords: MDR-1 gene; CYP3A gene; polymorphism; nephrotic syndrome; steroid responsiveness; childhood